Exploring the relationship between perceptual learning style preferences (PLSP) and foreign language class anxiety (FLCA) - Firissa, Berhanu; Gebremariam, Alamirew (Universitas Islam Malang, 2024)
The study investigating a relationship between perceptual learning style preferences (PLSP) and foreign language class anxiety (FLCA) remains limited, particularly regarding specific learning styles most impacted by FLCA and interventions to be tailored to reduce English class anxiety. The study examined the relationship between PLSP and FLCA among 110 grade eleven Mettu Comprehensive High School students. The study employed a PLSP questionnaire (Pashler et al., 2009) and an FLCA questionnaire (Horwitz et al., 1986) as the instruments. Data were collected, statistically analyzed, and interpreted using SPSS version 26. The study’s findings revealed that most participants' FLCA fell to the average higher level while those with group (PLSA-G) PLSP exhibited the least FLCA compared to participants with the individual (PLS-I) with the highest FLCA among the six dimensions of PLSP. Communication anxiety (FLCA-CA) significantly and fear of negative evaluation (FLCA-FNE) broadly were found to be the major sources of the participants’ sources of FLCA among its three dimensions in the scale. Furthermore, results of One-way ANOVA confirmed that PLSP is significantly and moderately related to FLCA. It was inferred that the constructs PLSP and FLCA play significant roles in the context of EFL teaching. Therefore, EFL instruction needs to address these variables as determinants of the learners’ success, and if meaningful pedagogical room is to be allocated, teaching practices need to pay attention to such. This area of exploration can lead to significant advancements in EFL pedagogy, creating a more inclusive and successful learning experience for students.